Pengujian Perppu oleh Mahkamah Konstitusi - Ni’matul Huda (The Constitutional Court of the Republic of Indonesia, 2016)
The authority to reviewing Perppu can not be obtained based on the interpretation of an institution or the situation that demanded the interpretation of a norm in the community, but must be strictly regulated in the constitution to the institution where authority was given, therefore there is no ‘juridical’ chaos in it.